(untitled) (Dhaka University Journal of Biological Sciences, 2013)
This study examined the present status of surface water pollution and a comparison of the quality of water in different seasons at different locations of the major river, around the Dhaka City. Field investigation was started from January, 2011 and sample collection was conducted six times at an interval of two months up to December, 2011. The observed value of different water quality parameters such as pH, DO, BOD, COD and TDS were compared with the standards recommended by Department of Environment (DoE), Bangladesh and United States Environmental Protection Agency (USEPA). A simple ANOVA and Box-Cox study was also conducted to detect the variation of water quality in the major rivers. The study revealed that during the dry season especially in the months of December to February (winter), the higher values of parameters with respect to the acceptable limits of DoE and USEPA standard indicate the pollution of the river water samples and make the water unsuitable for various uses. Comparisons of abundance values demonstrated high significant difference (p < 0.05) between the mean concentrations of respective parameters except pH at different locations in water source types. Water quality in Hagaribagh of Buriganga river and the Tongi railway bridge stations of Tongi khal was significantly more common polluted area than any other sites of selected water sources as the largest amounts of toxic chemicals are released here by the tannery and dyeing industries without any treatment. Dhaka Univ. J. Biol. Sci. 22(2): 145-154, 2013 (July)